Pengaruh Suhu Pemanasan Terhadap Aktivitas Antioksidan Selama Proses Pembuatan Beras Analog Dari Tepung Pisang Goroho - Yosua Taroreh; Christine F. Mamuaja; Jolanda C. E. Lamaega; Amanda Koleangan; Jenny E. A. Kandou; Riel J. J. Umboh (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
Goroho (Musa acuminata, sp) is a local banana variety from North Sulawesi characterized by high starch content and phenolic phytochemical compounds (polyphenols, flavonoids, and tannins) that possess potential antioxidant properties. Analog rice is a processed product developed as a substitute for conventional rice. This study aims to determine the effect of heating (drying) temperature on the antioxidant activity of Goroho during the production of analog rice from Goroho banana flour.The research utilized a Completely Randomized Design (CRD) with four drying temperature treatments: P1 (50°C), P2 (60°C), P3 (70°C), and P4 (80°C), each replicated three times. The observed variables included moisture content, bulk density, and antioxidant activity measured using the DPPH method. The results indicated that drying temperature significantly affected the moisture content, bulk density, and antioxidant activity of the Goroho analog rice. The highest antioxidant activity (indicated by the lowest, IC50) was achieved in treatment P1 (50°C) with a value of 65.33, while the lowest activity (highest IC50) was found in treatment P4 (80°C) with a value of 84.33. Furthermore, P1 (50°C) yielded the highest moisture content (17.33%) and bulk density (0.59 g/ml). Conversely, P4 (80°C) resulted in the lowest moisture content (6.66%) and bulk density (0.52 g/ml). Color analysis of the Goroho analog rice ranged from light cream to creamy yellow, with L* values between 76.7 and 82.2, a* values between -0.1 and 1.4, and b* values ranging from 3.5 to 8.8. Conclusion The study concludes that higher drying temperatures in the production of analog rice from Goroho flour lead to a decrease in antioxidant activity.